Discovery of small-molecule modulator of heterotrimeric Gi-protein by integrated phenotypic profiling and chemical proteomics. Issue 12 (1st December 2020) - Kawamura, Tatsuro; Futamura, Yushi; Shang, Erchang; Muroi, Makoto; Janning, Petra; Ueno, Masayoshi; Wilke, Julian; Takeda, Shigeki; Kondoh, Yasumitsu; Ziegler, Slava; Watanabe, Nobumoto; Waldmann, Herbert; et al.
ABSTRACT: Discovery of small-molecule inducers of unique phenotypic changes combined with subsequent target identification often provides new insights into cellular functions. Here, we applied integrated profiling based on cellular morphological and proteomic changes to compound screening. We identified an indane derivative, NPD9055, which is mechanistically distinct from reference compounds with known modes of action. Employing a chemical proteomics approach, we then showed that NPD9055 binds subunits of heterotrimeric G-protein Gi . An in vitro [ 35 S]GTPγS-binding assay revealed that NPD9055 inhibited GDP/GTP exchange on a Gαi subunit induced by a G-protein-coupled receptor agonist, but not on another G-protein from the Gαs family. In intact HeLa cells, NPD9055 induced an increase in intracellular Ca 2+ levels and ERK/MAPK phosphorylation, both of which are regulated by Gβγ, following its dissociation from Gαi . Our observations suggest that NPD9055 targets Gαi and thus regulates Gβγ-dependent cellular processes, most likely by causing the dissociation of Gβγ from Gαi . GRAPHICAL ABSTRACT: uf0001 By combining integrated phenotypic profiling and chemical proteomics, a small-molecule modulator of heterotrimeric Gi -protein was discovered.